RELIGIOUS LANGUAGE IN SEMIOTIC STUDIES - Rosmawaty Harahap (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
Philosophers who pursue the study of languages, such as JacquesDerrida, deny that the final language has meaning. Language is metaphor, so thatmeaning is always moving and changing incurred in accordance with the readinghorizon. Departing from this logic, if the language is a collection of religious texts(signs) for granted he does not know the meaning of the end.